Genetic and Biochemical Characterization of AXC-2 from Achromobacter ruhlandii - Papalia, Mariana Andrea (2024)
Achromobacter spp. are intrinsically resistant to multiple antibiotics and can also acquireresistance to those commonly used for the treatment of respiratory infections, especially in patients with cystic fibrosis. The aim of this study was to perform the genetic and biochemical characterization of AXC-2 from A. ruhlandii and to analyze all available AXC variants. Steady-state kinetic parameters were determined on a purified AXC-2 enzyme. It exhibited higher catalytic efficiencies towards aminopenicillins and older cephalosporins, while carbapenems behaved as poor substrates. Phylogenetic analysis of all blaAXC variants available in the NCBI was conducted. AXC was encoded in almost all A. ruhlandii genomes, whereas it was only found in 30% of A. xylosoxidans. AXC-1 was prevalent among A. xylosoxidans. AXC variants were clustered in two main groups, correlating with the Achromobacter species. No association could be established between the presence of blaAXC variants and a specific lineage of A. xylosoxidans; however, a proportion of AXC-1-producing isolates corresponded to ST 182 and ST 447. In conclusion, this study provides valuable insights into the genetic context and kinetic properties of AXC-2, identified in A. ruhlandii. It also provides a thorough description of all AXC variants and their association with Achromobacter species and various lineages.